The Coastal Turn in Romantic Studies - Pilz, Anna (Romanticism on the Net)

(untitled) (Université de Montréal, 2022)
This introductory article explores the opportunities opened up by a coastal turn in Romantic Studies. I analyse critical preoccupations in the connected fields of the environmental and blue humanities to make a case for the value of Coastal Studies to approach past and present coastal encounters. Scotland’s coast – the most expansive of Britain and Ireland – offers an exemplary case study to get into the prepositional ways of being on, of, by, and with the coast and to delve into the various forms through which they manifest in textual, visual, and material forms as lived-in environments that are shaped by artistic, colonial, economic, political, and scientific agendas. I suggest the year 1814 as a critical vantage point via readings of William Daniell and Walter Scott, whose works bring into focus the existence of multiple temporalities in coastal spaces, from the ancient to the ultra-modern and imagined future. By bringing together the voices of artists, critics, and curators and the material realities of Scotland’s coastal environments past and present, the special issue investigates the production of coastal knowledges two centuries ago as a process that informs twenty-first-century Romantic Studies. I argue that the coast emerges as a place and an environment that puts pressure on our understandings of genres, practices, and temporalities.